Comparison of clinical accuracy v/s investigations in the diagnosis of acute appendicitis - Halbhavi, Subhash N.; Lamni, Yamanur P.; Goudar, B. V.; Kalburgi, E. B.; T., Sushant P.; R., Manjula (International Surgery Journal, 2018)
Background: Now a day there is a trend to rely more on high-tech investigations rather than taking thorough history and clinical examination of the patients in the diagnosis of acute pain abdomen. Commonest cause of acute abdomen in the surgical practice is appendicitis. Delay in the diagnosis and treatment of acute appendicitis, leads to complications. Objective of this study was to evaluate the accuracy of clinical diagnosis versus sensitivity and specificity of ultrasound examination and histopathological examination of the resected specimen of appendix. This study also assesses the incidence of negative appendectomies in a medical college hospital of North Karnataka. Methods: This study included one hundred and fifty patients with history of pain abdomen where clinical diagnosis of acute appendicitis was made. The study period was of 18 months between February 2014 to July 2015. Routine blood investigations and abdominal ultrasonography were done in all cases. All ultrasound positive cases were subjected to surgery. Some ultrasound negative cases were also taken to surgery on the high suspicion of diagnosis of acute appendicitis depending upon thorough history taking and clinical examination. The diagnosis made depending on the ultrasound findings were compared with clinical findings, operative findings and histopathological examination reports. Results: Out of 150 patients, 104 were male and 46 were female. The common symptoms were pain in the RIF (100%) and anorexia (80%).The overall sensitivity and specificity of clinical diagnosis was 96.9% and 90.48% respectively. The same for ultrasound was 86.99% and 33.33% respectively. The present study shows negative appendectomy rate 6.66% in females and 7.33% in males. Conclusions: The diagnostic accuracy of ultrasound was 84.87% whereas clinical diagnosis was 96%. Thus, detailed history taking, and thorough clinical examination still holds good in the diagnosis of acute appendicitis and should be stressed in the clinical teaching.